Wavelength scaling of high-order-harmonic-generation efficiency by few-cycle laser pulses: Influence of carrier-envelope phase - (:unkn) unknown (AMER PHYSICAL SOC, 2012)
We investigate the wavelength scaling of high-order-harmonic-generation (HHG) efficiency by few-cycle laser pulses where the influence of the carrier-envelope phase (CEP) becomes prominent. Based on the numerical solution of time-dependent Schrodinger equation, in the infrared region of lambda (0.8-1.8 mu m), we observe that the power law of the form lambda (x) (x approximate to 5-6) is still present; but for constant intensity and a fixed energy interval, it differs markedly in the CEP. We find that for a specific value of CEP the wavelength dependence follows a lambda(-4.6) scaling in high-harmonic yield. We also perform classical trajectory calculations to gain some understanding of the CEP dependence of the wavelength scaling.